2005
DOI: 10.1007/11423348_8
|View full text |Cite
|
Sign up to set email alerts
|

A Trace Semantics for Long-Running Transactions

Abstract: Abstract. A long-running transaction is an interactive component of a distributed system which must be executed as if it were a single atomic action. In principle, it should not be interrupted or fail in the middle, and it must not be interleaved with other atomic actions of other concurrently executing components of the system. In practice, the illusion of atomicity for a long-running transaction is achieved with the aid of compensation actions supplied by the original programmer: because the transaction is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
105
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 5 publications
0
105
0
Order By: Relevance
“…We have compared two recent formal approaches to the modelling of compensable flow composition, that have been proposed independently in [5,7]. For the sequential case we have shown that the two frameworks essentially coincide by providing fully abstract encodings.…”
Section: Final Remarksmentioning
confidence: 99%
See 4 more Smart Citations
“…We have compared two recent formal approaches to the modelling of compensable flow composition, that have been proposed independently in [5,7]. For the sequential case we have shown that the two frameworks essentially coincide by providing fully abstract encodings.…”
Section: Final Remarksmentioning
confidence: 99%
“…Several proposals have recently appeared in the literature focused on the formalisation of compensable processes using process calculi. They can be roughly divided into two types: (i) compensable flow composition [6,5,7] closer to the spirit of orchestration languages like BPEL4WS, where suitable process algebras are designed from the scratch to describe the possible flow of control among services; and (ii) interaction based compensations [1,4,9,11], as suitable extensions of well-known name passing calculi, like the π-calculus and join-calculus, for describing transactional choreographies, where each service describes its possible interactions, and the actual composition takes place dynamically, i.e. when services interact.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations